The journey within : a meditative representation - Mahendran, Kalaimathi (2016)
This Final Year Project (FYP) is one that explored the symbolic visual language of the chakra system with its deeply rooted narrative counterpart. The research began from my curiosity in my own heritage and set of belief systems. Intrigued by the traditional influences in my way of life as a Hindu Indian I began to delve into the philosophy behind these values and morals. Questioning why and how do these visual languages communicate, if it does communicate how is it perceived now in comparison to the past. Systems, methodologies and expressions of various pictorials surrounding this ideology were the entry point from which this FYP research further expanded upon. In this paper in chronological order I would be talking about my heritage and cultural background. How such influences from a young age have molded me as an individual as well as how that in turn made me different, to how I subconsciously already decode and understanding symbolic references and imagery. To understand further beyond what existing information I already knew, I looked into Indian philosophical thoughts of beliefs and values; (The 5 Panchabutas) these are the 5 elements Indians believe made up the entire planet and the universe. With further reading came more connections that tied together universal representation with the human body. This is referenced with visual references as systems known as kundalini yoga already having been developed in the 18th to 19th century. The practice of yoga in the Indian culture not only connected the body and mind but also seeks to raise perception and awareness within oneself. How man has been represented as a simplification of the universe, spoken by the various geometric drawings and visualizations in regards to chakras and their forms. In summary studying the various layers of information embedded and attempting in reconnecting the dots between form and information that has been brushed off as superstition. This FYP has been a personal take on how I see this information. Categorising the various layers of information and drawing the links between the chakras and the various levels of experience and perception. This FYP is to communicate visually this visual representation of that meditative journey through which one’s energy travels between the states of chakra and how one changes with it.